Exploring the relationship between social functioning and executive function - Tay, Megan Su Eng (2017)
The relationship between social functioning and executive function has been closely investigated in recent years. These studies have approached the subject through exploring the association between the Theory of Mind (ToM) and executive function. However, the previous studies have primarily considered social functioning and executive function as unidimensional constructs. The findings from such research have been divergent and disagreed on the direction of influence in the relationship. This paper seeks to study the relationship between social functioning and executive function by examining the two constructs from a multidimensional perspective. We recruited 30 healthy subjects and assessed them on several domains including empathetic abilities, cool executive function, and hot executive function by the means of the Empathy Quotient scale, the counting Stroop task, and the Emotional-Continuous Performance Test. The results showed that empathetic abilities are associated with executive functions. Stepwise regression analyses revealed that: (i) cognitive empathy was a significant predictor of cool executive function performance; (ii) emotional reactivity and social skills were significant predictors of hot executive function performance. These findings suggest that the various sub-components of empathy, which are implicated in social functioning performance, have influence over our executive function.